Public Responses Towards Camera-Embedded Digital Signage Advertising - Sue-Hong Steven Wong; Meng-Chew Leow; Lee-Yeng Ong; Siong-Hoe Lau (JOIV : International Journal on Informatics Visualization, 2019)
This study proposes a measurable scale to gauge advertising effectiveness of digital signage. Gender study was performed on the constructs to supplement the findings. â€œEngagementâ€ and â€œInvolvementâ€, two well-known constructs were used to find out the advertising effectiveness using digital signage. A real-time experiment was conducted and the survey data (N = 221) were analysed, presenting descriptive analysis and T-test analysis across all items among the constructs. The findings reveal that both â€œEngagementâ€ and â€œInvolvementâ€ are significant contributors to advertising effectiveness in the context of digital signage. Findings also suggest that females tend to enjoy the advertisements more with higher degree of advertisement related experiences.